STRATEGI PENINGKATAAN LOYALITAS UPK GONDANGREJO KARANGANYAR - Adi Penawan; - Setiyana (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
Abstract, The purpose of this study was to analyze the product quality strategy, location, service quality, and promotion of customer loyalty UPK Gondangrejo Karanganyar. The population in this study was 1500 customers of UPK Gondangrejo Karanganyar. The analysis technique used is multiple linear analysis. With the random sampling method, a sample of 75 respondents was obtained. Questionnaire as an instrument for collecting data. Data analysis used the Classical Assumption Test, Linear Regression Test, t-test, f test, and R2 test. The classical assumption test results show the data can be justified. The regression test shows that product quality, service quality, and promotion have a positive effect while the location has a negative effect. The significance value of the t-test states that product quality, service quality, and promotion have a significant effect while the location has no significant effect. F test with a significance of 0.000 <0.05 shows that product quality, location, service quality, and promotion simultaneously have a significant effect. R2 test of 0.628 shows that product quality, location, service quality, and promotion have an effect on 62.8% of customer loyalty at UPK Gondangrejo Karanganyar. The results of this study are useful as a reference for future research. Keywords: Product and Service Quality, Promotions, Loyalty